819 PSEUDO-MOBITZ VAGAL ATRIOVENTRICULAR BLOCK: TWO CASE REPORTS IN YOUNG HEALTHY MEN. (15th December 2022) - Bonanno, Salvatore; Cocuzza, Federica; Carciotto, Gabriele; Marco, Paride Di; Ferrara, Nicola; Vetta, Giampaolo; Caminiti, Rodolfo; Parlavecchio, Antonio; Crea, Pasquale; Dattilo, Giuseppe; Luzza, Francesco; Carerj, Scipione; et al.
Abstract: We reported the cases of two young men with II degree AV block. The first one was a 17 yo asymptomatic boy, soccer player, undergoing 24 hours Holter-ECG for sporadic RVOT ventricular extrasystoles at resting ECG. During the night, an apparent Mobitz type 2 II degree AV block was observed. Detailed analysis showed: Sinusal bradycardia at 50 bpm; Absence of prolongation of P-R intervals before the pause; The pause is longer than double the basic P-P interval; Prolongation of P-P interval in the beats before the pause. The second case was also a young man suffering by atypical episodes of palpitations. The 24h Holter-ECG showed, during the night, an apparent Mobitz type 2 II degree AV block. Also in this case analysis of the tracing highlighted a) progressive slowing of sinus cycle length before the pause b) pause longer than double of sinus cycle and c) absence of prolongation of P-R intervals before the pause. Vagally mediated atrioventricular block and pseudo-Mobitz atrioventricular block. Vagally mediated AV block can have heterogeneous presentation: Wenckebach type, pseudo-Mobitz type II, 2:1, advanced-degree, complete AV block or a combination of different types of AV block and ventricular asystole. The mechanism is mediated by a vagal input, which depresses contemporarily sinus node and AV junction. The site of vagally mediated AV block is usually within the AV node. Generally, it results in a Wenckebach II degree AV block associated with sinus bradycardia, which occurs more often during the night in young/trained people. So the blocked P wave is generally preceded by Wenckebach phenomenon. However, in some patients the prolongation of the P-R interval is not present and the AV block appears abruptly. In these cases, Mobitz type II AV block may be erroneously diagnosed if sinus slowing is ignored. A differential diagnosis between true Mobitz II AV block and pseudo-Mobitz II block is essential for clinical purposes. Simultaneous slowing of the sinus rate and a pause longer than the double of the sinus cycle length indicate clearly a vagal mechanism, ruling out true Mobitz type 2 AV block, especially in young asymptomatic healthy men. In case of doubt, an electrophysiological study may be indicated.